Emptiness and Foolishness: spiritual disorder - Nizama Valladolid, Martin (2010)
It is realized a humanistic reflection about spirituality in the post modernity, whose knowledgement society shows as antonymous the emptiness, from what people escapes largely to materiality, the stupidity, foolishness , insensibility, hedonism and violence; that configure a decadent deshumanized society, in whose base underlie familiar unlove, lack of human value and antivalues anticipation in social ethos and lifestyles. The natural family model, source of love, is in extinction and is quickly exchanged by a modern, liberal and asistencialist family model, with lack of parents rol, who have lost their authority, protector and formative rol by the providing parents role. It is defined the concept of emptiness, its probably causes, its phenomenology and the fatuity social ethos is described. After that, foolishness and the social consequences of emptiness and foolishness, it is proposed an holistic focus and preventive and promotional aspects, realizing analyze and formuling some conclusions. Finally, there are seventeen examples of the empty generation.